Benefit of China's reduction in nitrogen oxides emission to natural ecosystems in East Asia with respect to critical load exceedance. (March 2020) - Xie, Danni; Zhao, Bin; Wang, Shuxiao; Duan, Lei
Highlights: The empirical critical loads of nitrogen for forests and grasslands in East Asia were mapped. The NOx emission abatement in China led to reduction in nitrogen deposition in East Asia. The area of critical load exceedance decreased in all contries in East Asia decreased. Abstract: The emission of nitrogen oxides (NOx ) in China decreased by 15% from 2010 to 2015 (without a significant decrease in NH3 emission), resulting in the decline of nitrogen (N) deposition in East Asia. Empirical N critical load exceedance was used to assess the benefit of the NOx emission reduction in China to natural ecosystems in East Asia. Empirical N critical loads for major forest and grassland types in East Asia were assigned based on field manipulation experiments for N effects. The critical load map based on the minimum of the critical load range of each vegetation type showed that empirical critical loads were generally lower in the Tibetan Plateau and some parts of northeastern China (≤5 kgN·ha −1 ·a −1 ), and higher in northern and southern China (≥20 kgN·ha −1 ·a −1 ). Empirical critical loads were also low in some parts of central and northern Japan (≤5 kgN·ha −1 ·a −1 ) and the south Korean Peninsula (5–10 kgN·ha −1 ·a −1 ). As a benefit of NOx emission reduction in China, N deposition in East Asia decreased significantly from 2010 to 2015. The total area and total amount of critical load exceedance in East Asia declined 4.6% and 14.3% respectively, suggesting great benefits to natural ecosystems.